3(y - 6)=15 como eu posso fazer isso
Soluções para a tarefa
Respondido por
1
Resposta:
y=11
Explicação passo-a-passo:
3.(y-6)=15
3y-18=15
3y=15+18
3y=33
y=33/3
y=11
Vamos verificar :
3.(y-6)=15
3.(11-6)=15
3.(5)=15
15=15
ok!
Espero ter ajudado!
Respondido por
1
Resposta:
3(y-6)=15
3y-18= 15
3y= 15+18
y= 33/3
y= 11
S= {11}
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Química,
10 meses atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás